The influence of work discipline, work motivation and work environment on employee performance (study at noms group, noms Kopi Semarang) - Rohmatun Khasanah; Sri Sudarsi (SEAN Institute, 2024)
The purpose of this study is to determine and analyze the Effect of Work Discipline, Work Motivation and Work Environment on Employee Performance of Noms Group, Noms Kopi Semarang The population of this study amounted to 110 employees, while the sample amounted to 92 employees. The sampling technique uses purposive sampling method. This study used a type of survey by distributing questionnaires to respondents. Data testing is carried out using validity tests, reliability tests, multiple linear regression analysis tests, f tests, coefficients of determination and t tests. The results of this study showed that partially work discipline did not have a significant effect on employees at Noms Group, Noms Kopi Semarang. However, partially, work motivation and work environment have a positive and significant effect on employee performance at Noms Group, Noms Kopi Semarang. In addition, simultaneously work discipline, work motivation and work environment have a positive and significant effect on employee performance at Noms Group, Noms Kopi Semarang.